White sorghum grain (Funk's G766W) and elevator-run red sorghum grain compared for fattening cattle - Drake, C.L.; Carlson, V.P.; Wilson, P.H.; Allen, Dell M. (Kansas State University. Agricultural Experiment Station, 2011)
An new white variety of sorghum grain (Funk’s G766W) has been reported to be higher in digestible dry matter and protein than elevator-run, rod sorghum grain. A 120-day field trial was conducted on the George and Vernon Miller farm near Great Bend to compare the two sorghum grain types under feed-lot conditions.
Keywords: Beef; White sorghum grain; Red sorghum; Feedlot performance